Landesaufnahme und Entwicklungsplanung im karibischen Tiefland Zentralamerikas - Nuhn, Helmut (ERDKUNDE, 1969)
This report sketches the geographical investigations that the author was able to carry out as advisor to the Instituto de Tierras y Colonizacion (ITCO) in Costa Rica and during private journeys in the neighbour countries of Central America. An introductory overview of the current situation and development of cartographic land survey is given. While the preparation of topographic maps is making good progress and is completed for the more densely-settled areas, thematic land survey is still restricted to individual projects, limited in their regional scope and content. The tasks, problems and up-to-date results of agrarian reform and guided colonisation in Central America make up the first focus of the research programme. In the course of the work, it was shown that agrarian social problems cannot be solved by the methods used up till now, given conditions of growing population pressure. The following sections deal with geographic regional investigations on the basis of thematic cartographic survey in northern Costa Rica and demonstrate their importance for the settlement of new land and for development planning. Using the ex ample of the amphibian landscape south east of Lake Nicaragua, the ecological problems of agricultural use and the adaptation of animal husbandry to the special conditions of the tropical lowland are briefly discussed (tropical trans humance). Remarks on the development up till now, on the structure and development possibilities of the Carib Low lands of Central America end the overview.